Addition of Tithonia Compost and Lime as Ultisol Soil Fertility Improvement for Oil Palm Sedling Media - Enita Enita; Nurhajati Hakim; Hermansah; Teguh Budi Prasetyo (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Research to improve soil fertility, especially the chemical characteristics of Ultisol, has been carried out by adding compost and lime. The incubation method of soil plus compost at a dose of 0.5 kg/pot – 2 kg/pot and 1x exchanged Al lime was carried out for 2 weeks. The results of soil nutrient analysis after incubation were an increase in pH of 0.58 points, a decrease in exchanged Al to unmeasured, an increase in the C-organic content of the soil by 3.44%, an increase in the total N-value of the soil by 0.19%, an increase in the amount of soil organic matter. P-available was 5.81 ppm and exchanged K soil increased by 0.02 me/100 g soil. Likewise, the micro elements analyzed also increase. Thus there is a change in the chemical properties of the soil towards the better. The increase in nutrients N, P, K, Ca, and Mg clearly comes from tithonia, which is the result of decomposition of tithonia compost which is added containing high nutrients. In addition, tithonia compost produces organic acids that can dissolve previously insoluble nutrients into soluble ones. The improvement of the chemical properties of the soil towards a better direction is expected to be able to increase the growth of oil palm seedlings planted on the seedling medium growing.